The Effect of Tax Planning, Company Growth and Investment Decisions on Company Value (Case Study on Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange in 2017-2020) - Dwi Ratna Sari; Putri Zanufa Sari (Journal of World Conference (JWC), 2022)
Companies always try to be able to pay taxes as low as possible by emphasizing tax costs, because taxes affect the reduction of income or net income, but for the government, taxes are increased to finance government administration. Property and real estate companies have become objects because currently property and real estate companies in Indonesia are growing rapidly and currently the investment trend that is developing in the community is investing money in land or property. The focus of the research is how the effect of tax planning, company growth and investment decisions on firm value in property and real estate companies listed on the Indonesia Stock Exchange. In this study, researchers used quantitative descriptive research. The variable used is the dependent variable with firm value (Y), and there are three independent variables, namely: Tax Planning (X1), Company Growth (X2), Investment Decisions (X3). The analytical method used in this research is multiple linear regression analysis which is processed using SPSS (Statistic Product and Services Solutions) version 26. The selected population is property and real estate companies listed on the Indonesia Stock Exchange in 2017-2020 with a purposive sample selection. sampling method through predetermined criteria. The total data used in this study consisted of 48 companies with a total of 192 data during the 4-year study period. The results of this study indicate that tax planning and investment decisions partially have a positive and significant effect on firm value and firm growth has no positive and significant effect on firm value. Simultaneously tax planning, company growth and investment decisions have a significant effect on firm value. The author limits the problem in this study by only using a sample of property and real estate companies listed on the Indonesia Stock Exchange in 2017-2020.